2019
DOI: 10.1037/bul0000186
|View full text |Cite
|
Sign up to set email alerts
|

Self-discrepancy theory as a transdiagnostic framework: A meta-analysis of self-discrepancy and psychopathology.

Abstract: Self-discrepancy theory (SDT) is a model of the relations between the self and affect which has been applied to the study of different types of psychopathology including depression, anxiety, and eating disorders. Although the theory itself is compatible with a transdiagnostic perspective on psychopathology, to date no systematic review of the literature has examined that possibility. We conducted a meta-analysis that synthesized the literature on self-discrepancy and psychopathology across a heterogeneous rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 109 publications
12
66
0
1
Order By: Relevance
“…Self‐discrepancy is an incongruity between how one currently perceives oneself and how one desire to view oneself (Barnett & Womack, 2015). These incongruities appear in social status (Harmon‐Jones, Schmeichel, & Harmon‐Jones, 2009), intelligence (Kim & Gal, 2014; Kim & Rucker, 2012), rights (Rucker & Galinsky, 2008, 2009), social group belonging (Loughran Dommer, Swaminathan, & Ahluwalia, 2013; Mason et al., 2019) and so forth. Mandel et al.…”
Section: Theory Development and Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐discrepancy is an incongruity between how one currently perceives oneself and how one desire to view oneself (Barnett & Womack, 2015). These incongruities appear in social status (Harmon‐Jones, Schmeichel, & Harmon‐Jones, 2009), intelligence (Kim & Gal, 2014; Kim & Rucker, 2012), rights (Rucker & Galinsky, 2008, 2009), social group belonging (Loughran Dommer, Swaminathan, & Ahluwalia, 2013; Mason et al., 2019) and so forth. Mandel et al.…”
Section: Theory Development and Research Hypothesismentioning
confidence: 99%
“…Compensatory consumer behaviour indicates any purchase, use or consumption of products or services motivated by a desire to offset or reduce a self‐discrepancy (Rucker & Galinsky, 2008). Whereas, when the self‐discrepancy decreases, consumers will practice corresponding consumption behaviours according to their own needs and expectations, as well as the requirements of their social status (Mason et al., 2019). In this study, we suggested that because of the influence of self‐discrepancy, the same PEB by consumers may arise from different sources of motivation.…”
Section: Theory Development and Research Hypothesismentioning
confidence: 99%
“…The perceived distance of the actual self from the ideal and/or ought self can have either positive (if the distance is small) or negative (if there is a large discrepancy) effects on affective states (Higgins, 1987). Indeed, research has demonstrated a link between actual/ought and actual/ideal discrepancies and different forms of psychopathology (see Mason et al, 2019 for a review).…”
Section: Fear Of Self In Eds: Empirical Supportmentioning
confidence: 99%
“…Additionally, given the importance of cognitive ED symptoms (Fairburn et al, 2003) and frequent co‐occurrence of depression and anxiety with BED (Hudson et al, 2007), we examined global ED psychopathology, depressive symptoms, and anxiety symptoms at follow‐up as secondary treatment outcomes. While ICAT‐BED and CBTgsh were associated with similar improvements in each of these secondary treatment outcomes in the recent trial comparing the two treatments (Peterson et al, 2020), evidence indicates that global ED psychopathology, depressive symptoms, and anxiety symptoms are each associated with self‐discrepancy (Mason et al, 2019), self‐directed style (Mason et al, 2016), and emotion dysregulation (Aldao, Nolen‐Hoeksema, & Schweizer, 2010; Hofmann, Sawyer, Fang, & Asnaani, 2012). Thus, regardless of intervention type, changes during treatment in these hypothesized binge‐eating maintenance mechanisms from the ICAT model may also impact global ED psychopathology and symptoms of depression and anxiety.…”
Section: Introductionmentioning
confidence: 97%